Faktor Penghambat Kepolisian Resor Gorontalo Dalam Penanganan Dugaan Kepemilikan Batu Hitam Yang Ditemukan Di Kecamatan Pulubala: (Studi Kasus Tipidter Polres Gorontalo) - Nurmala Unti; Lisnawaty W. Badu; Jufryanto Puluhulawa (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The Indonesian government requires a Mining Business License (IUP) for mining activities as regulated in Law Number 3 of 2020 concerning Mineral and Coal Mining (UU Minerba). The discovery of black stones in large quantities and indications of being the result of illegal mining activities is a serious problem that must be handled properly. In uncovering cases of ownership of mining products, police efforts are very important in uncovering networks of perpetrators of violations in the mining sector. The problems raised in this research are: What factors hinder the Gorontalo Resort Police in handling allegations of ownership of black stones found in Pulubala District. This research is directed at empirical legal research and the approach used in this research uses a statutory regulation approach and a case approach. This research was carried out at Gorontalo Police. The research results show that the inhibiting factors in handling allegations of black stone ownership in Pulubala District are limited personnel in the police Tipidter unit, the number of cases exceeding personnel capacity, limited time, budget for investigations, lack of cooperation from witnesses and suspects, as well as a lack of facilities and infrastructure. in carrying out the investigation process.